PPARγ activator, rosiglitazone: Is it beneficial or harmful to the cardiovascular system? - Palee S. (2014)
Rosiglitazone is a synthetic agonist of peroxisome proliferator-activated receptor γ which is used to improve insulin resistance in patients with type II diabetes. Rosiglitazone exerts its glucose-lowering effects by improving insulin sensitivity. Data from various studies in the past decade suggest that the therapeutic effects of rosiglitazone reach far beyond its use as an insulin sensitizer since it also has other benefits on the cardiovascular system such as improvement of contractile dysfunction, inhibition of the inflammatory response by reducing neutrophil and macrophage accumulation, and the protection of myocardial injury during ischemic/reperfusion in different animal models. Previous clinical studies in type II diabetes patients demonstrated that rosiglitazone played an important role in protecting against arteriosclerosis by normalizing the metabolic disorders and reducing chronic inflammation of the vascular system. Despite these benefits, inconsistent findings have been reported, and growing evidence has demonstrated adverse effects of rosiglitazone on the cardiovascular system, including increased risk of acute myocardial infarction, heart failure and chronic heart failure. As a result, rosiglitazone has been recently withdrawn from EU countries. Nevertheless, the effect of rosiglitazone on ischemic heart disease has not yet been firmly established. Future prospective clinical trials designed for the specific purpose of establishing the cardiovascular benefit or risk of rosiglitazone would be the best way to resolve the uncertainties regarding the safety of rosiglitazone in patients with heart disease.